Risikopositionswert einer derivativen Adressen-Risikoposition: Darstellung der bisherigen sowie der neuen Berechnungsmethoden - Waschbusch, Gerd; Reinstädtler, Gabriela; Biehl, Jonathan, M.Sc.; Burr, Julius, M.Sc. (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
This book deals in detail with the methods used to calculate the risk position value of a derivative counterparty risk position at institutions. To this end, it first examines the term risk, focusing especially on counterparty risks. Subsequently, it addresses the basics of quantifying counterparty risk, focusing principally on the treatment of a derivative counterparty risk position. Based on this, the previous and new methods of calculating the risk position value of a derivative counterparty risk position are presented in detail. Finally, the authors assess the significance of the risk position value of a derivative counterparty risk position in determining the overall amount of risk and the regulatory minimum capital ratios.